City of lies [videorecording (DVD)] - Depp, Johnny; Whitaker, Forest; Huss, Toby, 1966-; Callie, Dayton; Sullivan, Randall (Lionsgate, 2021)
This crime-thriller follows the investigation into the infamous murder of iconic rap artist Christopher Wallace aka The Notorious B.I.G. Determined LAPD detective Russell Poole spent nearly 20 years trying to solve the murder, and Jack Jackson, a journalist teams up with Poole in search of the elusive truth. Together they explore why the case remains old, and why a secretive division of the LAPD is seemingly set on keeping it that way.